CD11c+CD8alpha+ dendritic cells promote protective immunity to respiratory infection with Bordetella pertussis. - MILLS, KINGSTON; MORAN, BARRY (The American Association of Immunologists, 2009)
CD11c+CD8?+ and CD103+ DC have been shown to promote regulatory T cell responses and mediate tolerance in the gastrointestinal tract. These cells have also been identified in the lung, but their role in immunity to respiratory tract infection is not clear. Here we have used a murine model of infection with Bordetella pertussis to examine the function of DC subtypes in protective immunity in the lungs. We found a dramatic increase in the numbers of CD11c+CD8?+ DC in the cervical lymph nodes (CLN) within 4 hrs of challenge with B. pertussis and these DC could acquire particulate antigen from the upper respiratory tract. CD11c+CD8?+ DC also infiltrated the lung with a peak 7 days post B. pertussis challenge. The infiltrating CD11c+CD8?+ DC expressed MHC, co-stimulatory and activation markers, indicative of mature DC. The CD11c+CD8?+ DC in the CLN expressed IL-4 and IL-10, and lower levels of IFN-?, but in the lungs expressed predominantly IFN-?. Depletion of CD8?+ cells early in infection attenuated Th1 responses in the lungs and significantly reduced bacterial clearance. Conversely, transfer of FLT3 ligand (FL)-expanded CD11c+CD8?+ DC enhanced bacterial clearance, whereas GM-CSF-expanded conventional DC had no effect. The numbers of CD11c+CD8?+CD103+ cells were also increased during the early phase of infection. Blocking CD103 function caused a significant delay in bacterial clearance and a reduction in cellular infiltration into the lungs. These findings demonstrate that CD11c+CD8?+ and CD11c+CD103+DC play a protective role in mediating immunity to B. pertussis infection in the respiratory tract.
PUBLISHED
Keywords: Biochemistry